Nilai Cipta-sama Sistem Pengurusan Pembelajaran (Sains Humanika, 2013)
The purpose of this study is to identify the value co-creation of a Learning Management System. Data were collected through a Laddering Technique based on Means-End Chain Theory, Service Dominant Logic and Rokeach Value List (1973). Value co-creation elements are important to identify the critical feature during the design process of the Learning Management System. A number of 30 respondents were selected using purposive data sampling technique. This is a case study based on Sistem Pengurusan Pengajaran & Pembelajaran Interaktif, UKM (SPIN). Research findings listed six value co-creation elements consists of self directed, capability, intellectual, ambitious (hardworking), responsibility and helpful. The findings were shown in an implication matrix and Value Hierarchy Map (VHM). Significant of the study is to help identify co-creation value based on critical features such as Lecture Notes, Annoucement and Course Profile. These critical features are able to provide great impact on the success of a Learning Management System. The research findings could be developed into a generic model of value co-creation model.
Keywords: Laddering technique; learning management system; value co-creation; means-end theory; servic dominant logic